Recovering the H ii region size statistics from 21-cm tomography. Issue 2 (22nd June 2017) - Kakiichi, Koki; Majumdar, Suman; Mellema, Garrelt; Ciardi, Benedetta; Dixon, Keri L.; Iliev, Ilian T.; Jelić, Vibor; Koopmans, Léon V. E.; Zaroubi, Saleem; Busch, Philipp
Abstract: We introduce a novel technique, called 'granulometry', to characterize and recover the mean size and the size distribution of H ii regions from 21-cm tomography. The technique is easy to implement, but places the previously not very well-defined concept of morphology on a firm mathematical foundation. The size distribution of the cold spots in 21-cm tomography can be used as a direct tracer of the underlying probability distribution of H ii region sizes. We explore the capability of the method using large-scale reionization simulations and mock observational data cubes while considering capabilities of Square Kilometre Array 1 (SKA1) low and a future extension to SKA2. We show that the technique allows the recovery of the H ii region size distribution with a moderate signal-to-noise ratio from wide-field imaging (SNR ≲ 3), for which the statistical uncertainty is sample variance dominated. We address the observational requirements on the angular resolution, the field of view, and the thermal noise limit for a successful measurement. To achieve a full scientific return from 21-cm tomography and to exploit a synergy with 21-cm power spectra, we suggest an observing strategy using wide-field imaging (several tens of square degrees) by an interferometric mosaicking/multibeam observation with additional intermediate baselines ( ∼ 2-4 km) in an SKA phase 2.